Interaksi Sosial Rekan Kerja Dengan Intensi Turnover Karyawan - Vitri Yuniarti; Alif Dian Cahyaningtyas (Universitas Darul Ulum, 2021)
The purpose of this study is to determine whether there is a relationship between the social interaction between coworkers and employee turnover intentions.The hypothesis proposed is that there is a link between the social interaction between colleagues and employee turnover intentions. Research subjects were 50 employees of PT. Xuilong Outdoor Tunggorono recruited through the Purposive random sampling technique. The independent variable chosen was the social interaction between colleagues. While, the dependent variable is the Turnover Intention. The data collection tools consist of a social interaction scale and a Turn over intention scale. Analysis of hypothesis testing using Spearman's Rho correlation analysis. Result of research rho XY = 0,-234; with p = 0.102 (p > 0.05). This indicates that the hypothesis is rejected, meaning that there is no correlation between Social Interaction among Coworkers and Employee Turnover Intentions at PT. Xuilong Outdoor Tunggorono Jombang Keywords: Social Interaction: Turnover Intention